2021
DOI: 10.2144/fsoa-2020-0169
|View full text |Cite
|
Sign up to set email alerts
|

Oncofertility Care in Young Women and the Outcomes of Pregnancy Over the Last 5 Years

Abstract: Aim: To ascertain the actual outcomes of oncofertility care in young women to provide more appropriate care. Materials & methods: We analyzed the data of 67 female patients under 43 years of age who underwent oncofertility care between January 2015 and September 2019. Results: There were 28 patients with breast cancer, 19 patients with hematologic cancer and 20 patients with other cancer diagnoses. Breast cancer patients tended to take longer than hematologic cancer patients to initiate oncofertility treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…analyzed the data of 67 Japanese women aged < 43 years who underwent oncofertility care. The study indicated that as spontaneous pregnancies were more common than ART pregnancies, pregnancy via not only ART, but also via the non-ART method is a viable option for young cancer survivors [14]. In our study, 40 live births were reported, and three patients had live births from pregnancies induce via embryo transfer.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…analyzed the data of 67 Japanese women aged < 43 years who underwent oncofertility care. The study indicated that as spontaneous pregnancies were more common than ART pregnancies, pregnancy via not only ART, but also via the non-ART method is a viable option for young cancer survivors [14]. In our study, 40 live births were reported, and three patients had live births from pregnancies induce via embryo transfer.…”
Section: Discussionmentioning
confidence: 65%
“…In recent times, post-treatment life events, such as pregnancy and childbirth, have been considered an essential part of treatment planning for adolescent cancer patients because advances in cancer therapy have substantially increased the long-term survival rate of adolescent and young adult cancer survivors [14]. However, this issue remains unclear because there is insu cient data, especially in thyroid cancer patients with DM.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of pregnancy after breast cancer treatment is greatly affected by patient age; most of pregnancies are established within a short period of time after the woman is permitted to attempt conception or infertility treatment. It is also important information that spontaneous pregnancy can be expected after treatment for breast cancer if the patient is under 35 years of age as reported previously; it is important for patients over 35 years of age to move toward ART in a timely manner 20 . Therefore, we deem it desirable to determine the optimal duration of TAM therapy for patients with breast cancer who wish to become pregnant when oocyte/embryo was not preserved.…”
Section: Discussionmentioning
confidence: 89%
“…It is also important information that spontaneous pregnancy can be expected after treatment for breast cancer if the patient is under 35 years of age as reported previously; it is important for patients over 35 years of age to move toward ART in a timely manner. 20 Therefore, we deem it desirable to determine the optimal duration of TAM therapy for patients with breast cancer who wish to become pregnant when oocyte/embryo was not preserved. This study was analyzed by grouping by age at the end of breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 The process of controlled ovarian hyperstimulation takes approximately 14 days, but the time required has neither been shown to significantly delay treatment initiation, nor increase rates of cancer mortality or recurrence. 7,8 To effectively provide FP services in a streamlined manner for patients diagnosed with cancer, guidelines recommend that physicians who are treating reproductive-age patients with cancer have rapid access to a point of contact for FP referral, an interdisciplinary medical team of adolescent and young adult specialists, oncologists, and reproductive specialists, a year-round experienced embryology laboratory qualified for cryopreservation, and counselors for mental health, genetics, and finances. 5 Female cancer survivors who receive fertility counseling prior to initiating gonadotoxic therapy have been shown to have decreased regret and improved quality of life, highlighting the importance of FP care in optimizing longterm care in cancer survivors.…”
mentioning
confidence: 99%